Mediation of Business Competency on The Effect of Culinary MSME Incubation Training on Business Success - Rizky, Fahmi Muhamad; Ningsih, Caria (Politeknik Pariwisata Lombok, 2026)
Introduction: Culinary MSMEs are the most popular businesses for tourism and creative economy businesses in Indonesia. The high public interest in culinary businesses is supported by government support, one of which is the Culinary Incubation organized by the Indonesian Ministry of Tourism and Creative Economy. This study aims to examine the extent to which the role of business competency in mediating the effect of Culinary Incubation training on business success. Business competence was chosen as a mediator because it is a key factor linking training to business success, where increased competence through training can encourage entrepreneurs to manage their business more effectively and innovatively. Methodology: The research approach used is a quantitative approach with data collection techniques through questionnaires distributed via e-form, The population in the study were all 30 participants of the Borobudur Culinary Incubation training, so that the entire population was sampled in this study. The data analysis technique uses the partial least square model (PLS-SEM) with the SmartPLS 4.0 program. Findings: The results of this study indicate (1) training has a significant positive effect on business success, (2) training has a significant positive effect on business competency, (3) business competency has a significant positive effect on business success, and (4) business competency mediates positively and significantly on the effect of training on business success. Conclusion: The results of this study can be a reference for culinary MSMEs and training organizers in improving business competencies and business success. This study contributes to the literature by validating the mediating role of business competency in the MSME incubation context, particularly in Indonesia's culinary sector. Beyond empirical validation, this research provides a novel perspective by highlighting business competency as a critical mechanism that links incubation training to sustainable business success, thereby enriching human capital theory and offering a theoretical contribution to entrepreneurial learning in emerging economies.